Zbiór kodeksów („biblioteka”) z Nag Hammadi. Stan badań i nowe kierunki poszukiwań (Przegląd Religioznawczy – The Religious Studies Review, 2021)
The author divided his paper into two parts. In the first one he shows issues concerning a whole of the Nag Hammadi collection as to which a certain consensus have been reached by the scholars. These are, i.a.: division into subcollections, diversity in term of the dialects of the Coptic language, different literary forms, belongingness to various religious and ideological traditions, main thematic threads and ritual practice. In the second part he presents directions of research and fields of discussions which from 2010 have appeared in connection with the collection of the Nag Hammadi codices. These are issues like: the hypothesis that the collection came into being in milieu of Pachomian monks, or that it is grave goods of a wealthy person, and a few others. The author also notices a shift of focus from “Gnosticism” of 2nd and 3rd centuries to Egyptian culture of 4th and 5th centuries as regards research on said collection. The main conclusion of this paper is that the collection of the Nag Hammadi codices is step by step becoming an independent subject of study.